POLICE AUTHORITY IN ENVIRONMENTAL POLLUTION CRIMES: THE USE OF DISCRETION IN THE INVESTIGATION PROCESS - Lega Ikhwan Herbayu; Lesza Leonardo Lombok; Arthur Novy Tuwaidan (International Journal of Applied Science and Sustainable Development (IJASSD), 2025)
The police as law enforcement officers who are given the authority to carry out inquiries and investigations based on statutory regulations must be able to understand the various problems contained in the Environmental Protection and Management Law. One of the reasons for using discretion in investigating criminal acts in the environmental sector is the lack of PPNS (Civil Servant Investigator) resources in the area where the crime occurred to carry out the investigation. For the sake of effectiveness and efficiency of investigations, Police Investigators take a discretionary policy by carrying out their own investigations by only taking expert information from experts in the environmental field. Therefore, this research aims to find out and analyze the authority of the police in investigating environmental crimes, and to understand and analyze the implementation of police discretion in the process of investigating environmental crimes. Using normative legal method, the author finds that the authority of the Police in investigating environmental crimes is considered to be the same as the authority obtained in the Criminal Procedure Code, with several mechanisms in the the Environmental Protection and Management Law, but with procedures in the provisions of Regulation of the Chief of Police of the Republic of Indonesia. Police discretion in investigating environmental crimes needs to be exercised because it provides flexibility for the police in dealing with various complex and dynamic situations in environmental crimes.